Taktisk planering med geografisk hänsyn : fallstudie med Heureka PlanVis på SCA Skogs distrikt Liden - Johansson, Håkan (SLU/Dept. of Forest Resource Management, 2012)
SCA is the largest private owned forest owner in Sweden, with an ownership of 2 million hectares of productive forestland. To manage the planning of such large areas and to fit the traditional organization structure of a Swedish forest company, the planning approach is subdivided into three stages; strategic, tactical and operational. The strategic part, based on a statistic sample of stands, returns a harvest level estimate which should then be implemented at actual sites in the tactical part. This procedure can lead to incompatible solutions as the strategic solution is not necessarily possible to translate into actual sites in the tactical plan. The geographic aspect is important in tactical planning due to the large costs for moving equipment and maintenance of a large number of forest roads. The aim of this study was therefore to develop a model that considers geographic location to an existing road network, and to examine if the software Heureka PlanWise can be used to strengthen the link between strategic and tactical planning. By using PlanWise with comprehensive data for both strategic and tactical planning, the boundary between the two was reduced, leading to a larger compatibility between the plans. The tactical model, provided with a road access cost, was used to control the degree of clustering of harvest activities within the existing road network. Specific harvest volumes per species and seasons were defined for final felling. Results show that the model can control the degree of clustering, but specific settings should be elaborated further for an actual application at the host company.